Hubungan antara Optimisme dan Distres Psikologis pada Emerging Adults Miskin di DKI Jakarta - Chelsea Dimeitri Angelica Hutapea; Sri Fatmawati Mashoedi Mashoedi (Fakultas Psikologi Universitas Pancasila, 2019)
The poor and emerging adults groups are vulnerable to psychological distress. This study aims to examine the relationship between optimism and psychological distress among poor emerging adults in DKI Jakarta. Optimism was measured by the Life Orientation Test-Revised (LOT-R) and psychological distress measured by Hopkins Symptoms Checklist-25 (HSCL-25). The participants in this study were 261 with age range of 18-29 years old, consisting of 92 (35,2%) man and 169 (64,8%) women. With Pearson Correlation analysis, it was found that optimism had a significant relationship with psychological distress (r(259) = -0,161, p = 0,009, two-tailed) and r2 = 0,026.